Affinity purification and characterization of a yeast epoxide hydrolase - Botes, A.L (Biotechnology letters, 1999)
Purification of the membrane-associated epoxide hydrolase from the yeast Rhodosporidium toruloides CBS 0349 to electrophoretic homogeneity was achieved in a single chromatographic step employing the affinity ligand adsorbent Mimetic Green. More than 68% of the total epoxide hydrolase activity present in the whole cells was recovered from the membrane fraction. The enzyme was purified 26-fold with respect to the solubilized membrane proteins and was obtained in a 90% yield. The purified epoxide hydrolase has an apparent monomeric molecular weight of approximately 54 kDa, and a pI of 7.3. The enzyme was optimally active at 30-40 degrees C, and pH 7.3-8.5. The enzyme is highly glycosylated with a carbohydrate content >42%. The specific activity of the purified enzyme for (+/-)-1,2-epoxyoctane is 172 micromol min(-1) mg protein(-1). The amino acid composition of the protein was determined. This is the first report of a yeast epoxide hydrolase purified to homogeneity in milligram amounts.